IMPLEMENTASI PENDEKATAN DEEP LEARNING PADA PEMBELAJARAN PAI DI SMA MUHAMMADIYAH 4 JAKARTA - Nur Hanifah, Ika Karenina; Muhammad Arifin Rahmanto (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study examines the implementation of a deep learning approach in Islamic Religious Education (PAI) at SMA Muhammadiyah 4 Jakarta. The study aims to explore teachers’ and students’ learning experiences and to analyze the application of Mindful, Meaningful, and Joyful Learning strategies integrated with Al-Islam and Kemuhammadiyahan (AIK) values. A qualitative descriptive design with a phenomenological approach was employed to understand the meaning of learning experiences within the context of modern Islamic education. Data were collected through observation, interviews, and documentation, and analyzed using the interactive model of Miles and Huberman. The findings indicate that the implementation of deep learning fosters holistic learning experiences by integrating cognitive, affective, and spiritual dimensions. Students are able to connect Islamic teachings with everyday life, develop religious awareness, and engage in reflective and enjoyable learning activities. Institutional support through Muhammadiyah educational structures and ISMUBA traditions contributes to curriculum alignment with school culture and the characteristics of urban learners. Overall, the study demonstrates that deep learning integrated with AIK values strengthens PAI as a holistic living curriculum and provides implications for improving Islamic education practices.